Advanced Numerical Techniques to Design T-bonded Joints - Moreira , F. J. P.; Campilho , R. D. S. G. (Technological Innovation in Engineering Research Vol. 4, 2022)
The use of adhesive bonds greatly increased in industrial applications, as they have multiple advantages compared to other more traditional bonding methods (fastened, welded and riveted joints). The number of approaches to predict the strength of adhesive joints has increased over the years. The eXtended Finite Element Method (XFEM) is a recent variant of the (Finite Element Method) FEM to model damage growth in structures, although it is yet seldom studied within the context of bonded joints. This research includes of an experimental and XFEM investigation of three adhesively bonded aluminium alloy T-joints. The thickness of the curved adherends (tP2) is studied parametrically, with values ranging from 1 to 4 mm. Different damage initiation and propagation criteria were used to assess the XFEM prediction capabilities. It was discovered that correct numerical results can be found if the modeling conditions are appropriately set.